Characterisation of stormwater in biomass-fired combined heat and power plants – Impact of biomass fuel storage. (15th May 2016) - Larsson, Magnus; Yan, Jinying; Nordenskjöld, Carl; Forsberg, Kerstin; Liu, Longcheng
Highlights: Stormwater is characterised for a biomass-fired CHP plant. An evaluation method is developed to combine general methodology with on-site features. Runoff water are evaluated by experimental investigation combined with modelling/simulation. Impacts of biomass fuel storage on runoff water quantity and quality are analysed. The results provide basic data for a sustainable development of energy–water–environment nexus. Abstract: Characteristics of stormwater in industrial areas are evaluated, specifically based on a biomass-fired combined heat and power (CHP) plant with on-site biomass fuel storage. An evaluation method is developed to combine general methodology applied for stormwater characterisation with the on-site features of the biomass-fired CHP plant. Investigations were carried out through on-site monitoring and laboratory experiments with the defined methodology. Recycled wood chips as biomass fuel currently used in Swedish biomass-fired CHP plants have been used as an example for this study. The impacts of outdoor biomass fuel storage have been analysed for both runoff water quantity and quality. The results indicate that the properties of stored biomass fuels will significantly affect the runoff quantity by its water absorption capability. The overall runoff quality is highly depended on precipitation intensity and the runoff volume from the biomass storage piles, which is influenced by the water retention capacity and leaching ability of biomass fuels. The practical data and information presented in this paper can be used to understand the principal issues and the most important factors for internal control of contamination sources in order to achieve sustainable Energy–Water systems for bioenergy conversion in biomass-fired CHP plants.